PENGEMBANGAN E-MODUL PRAKTIKUM BERBASIS PROBLEM BASED LEARNING PADA MATA KULIAH PRAKTIK MOTOR BAKAR LANJUT DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNS - Fuad Dwi Mustofa; Husin Bugis; Valiant Lukad Perdana Sutrisno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to (1) produce a practical teaching material in the form of a practicum e-module for advanced fuel motor practice courses in the Mechanical Engineering Education Study Program which is declared feasible (2) find out the practicality of practicum e-modules in advanced fuel motor practice courses in the Mechanical Engineering Study Program.This research uses the type of research development or Research and Development (R&D). The development model used is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this study included practicum e-module requirement sheets, practicum e-module validation sheets by experts, research sheets for lecturers in advanced fuel motor practice courses and student response sheets. Trials of the practicum e-module product were carried out for students of the Mechanical Engineering Education study program class of 2021 who are currently taking an advanced fuel motor practice course. Data analysis used in this research is descriptive quantitative and descriptive qualitative.Based on the results of the analysis of the validation sheet by the experts, it was found that the practicum e-module was declared feasible to use with a score of 88.8% for the results of material experts in the very feasible category, 86.4% for media experts in the very feasible category, and linguists showing a percentage score of 97.5% very decent category. Based on the results of the analysis of the practicum e-module practicum sheet by student responses and the assessment of lecturers supporting advanced fuel motor practice courses, it shows that the practicum e-module is stated to be practical with an average result of student response percentage scores of 88.9% in the very practical category and the assessment of supervising lecturers shows a score of 85.3% with the very practical category. So that the practicum e-module is declared feasible and practically used by students as teaching material in supporting the learning of advanced fuel motor practice course.